Demand Patterns in France, Germany, and Belgium : Can We Explain the Differences? - Lebrun, Igor.; Perez Ruiz, Esther (Washington, D.C. : International Monetary Fund, 2014)
The need to revive Euro area growth highlights the importance of the evolution of domestic and external demand in the core. This paper puts recent demand patterns in France, Germany, and Belgium into historical perspective. We find that, first, dynamics for private consumption, non-residential business investment, and exports since 2008 is dominated by conventional determinants, with no discernible structural break as a result of the crisis. Second, although country-specific factors matter in some cases, demand patterns in these countries are largely driven by common determinants. Third, developments in common fundamentals tend to dominate demand dynamics, coupled, in a few cases, with structurally different elasticities across countries. Fourth, short-term analysis suggests a role for confidence and uncertainty factors in explaining temporary deviations of these variables from long-term fundamentals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet